Influence of geometry of the impenetrable electrodes on process of formation of the current crisis in the plasma accelerators - Kozlov, A.N. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
This paper reports the results of the numerical studies of the axisymmetric flows in the plasma accelerators with the impenetrable equipotential electrodes of the various geometries. The calculations were performed using the two-dimensional two-fluid magnetohydrodynamic model taking into account the Hall effect and the conductivity tensor of the medium. The numerical experiments have allowed to reveal the influence of the electrode form on effect of occurrence of the current crisis.